Tunable perfect optical absorption in truncated photonic crystals with lossy defects - Yan, Runze; Li, Junyang; Zhou, Haiyang; Zhao, Ying; Liu, Fen; Wu, Ailing; Du, Guiqiang (Frontiers in Physics, 2022)
We theoretically investigate tunable optical absorption properties of photonic crystals containing lossy materials as defects. It is found that a lossy defect can induce one or multiple perfect absorption peaks in the bandgap of photonic crystals and the number of the peaks mainly depends on the thickness of the defect layer. On the other hand, multiple complete absorption peaks can also emerge in the photonic bandgap when multiple lossy defects are inserted within the photonic crystals, and the resonant wavelengths of absorption peaks can be modulated by changing the distances among the defects. On the other hand, the optical absorption away from resonant wavelengths is nearly zero in whole visible range. Such nanostructures can be used to engineer novel optical devices such as tunable single-channel and multi-channel perfect optical absorbers.